Intrahousehold allocation and gender relations: new empirical evidence from four developing countries - Quisumbing, Agnes R.; Maluccio, John A. (International Food Policy Research Institute, 2000)
The paper reviews recent theory and empirical evidence testing unitary versus collective models of the household. In contrast to the unitary model, the collective model posits that individuals within households have different preferences and do not pool their income. Moreover, the collective model predicts that intrahousehold allocations reflect differences in preferences and ""bargaining power"" of individuals within the household. Using new household data sets from Bangladesh, Indonesia, Ethiopia, and South Africa, we present measures of individual characteristics that are highly correlated with bargaining power, namely human capital and in ividually-controlled assets, evaluated at the time of marriage. In all country case studies we reject the unitary model as a description of household behavior, but to different degrees. Results suggest that assets controlled by women have a positive and significant effect on expenditure allocations toward the next generation, such as education and children's clothing. We also examine individual-level education outcomes and find that parents do not have identical preferences toward sons and daughters within or across countries.